The concept "salvation" in the Church of Scientology - Pretorius, S. P. (HTS teologiese studies, 2006)
In one of its publications the Church of Scientology (COSI), a well-established religious movement in South Africa, claims to be not only the fastest growing religious movement, but also to be an active force for positive change in the world. The Church of Scientology’s utilization of familiar terms such as “church” and “religion” can be misleading. It can create the understanding with some that Scientology might be related to, or even be an extension of the Christian tradition. This understanding is further enhanced by their assurance to Christians that joining the church will not distance them from, but instead, strengthen their own faith. This article, however, concludes that closer investigation of the philosophy of Scientology indicates that there is a distinct difference between the salvations offered by Scientology and that of the Christian tradition.